OPTIMASI KOMBINASI ASPARTAM- TROPICANA SLIM® SEBAGAIPEMANIS DALAM FORMULASI TABLET EFFERVESCENT DARI EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) DENGAN METODE SIMPLEX LATTICE DESIGN - Angga Aprilianto (Universitas Islam Indonesia, 2016)
Flower calyces Rosela (Hibiscus sabdariffa L) is a traditional medicine as anti-hypertension is now widely used in various preparations. This research alms to create effervescent tablets of flower calyces extract Rosela (Hibiscus sabdariffa L) with a stable characteristic of simplex lattice design method. Formula optimization used simplex lattice design because this method does not require much effort and money. Then extracts are tested their physical properties including appearance, viscosity, and moisture content. Granules obtained are tested it flow time. While testing physical properties include the effervescent tablet weight uniformity, tablet hardness, friability, and time dissolve tablet in water. To get the equation to obtain the profile properties - the physical properties of effervescent tablets, then the simplex lattice design based on the formula that made three Fl (aspartame 50%: 50% Tropicana Slim®), Fll (aspartame 100%: 0% Tropicana Slim®) and Fill (0%aspartame: 100% Tropicana Slim®). Formula optimization is done by using variable hardness, friability, and time dissolve with each - each coefficient of 0.33, 0.32, 0.35. From the results of optimization using simplex lattice design method obtained a total response value (R)Is the concentration of aspartame 40%: 60% Tropicana Slim® which is the optimum formula. Besides the active compounds of flavonoids routine can still be found in the effervescent tablet is produced. Respondents most preferred formula is formula II, with 50% aspartame and 50% Tropicana Slim®.